Calculation and Optimization of Plasma Utilization Process of Inflammable Wastes after Spent Nuclear Fuel Recycling; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Karengin A. G. Aleksandr Grigorievich; Karengin A. A. Alexey Alexandrovich; Novoselov I. Yu. Ivan Yurievich; Tundeshev N. V. Nikolay Vladislavovich (Chemical Technologies, 2014)
Title screen